Influência da adubação mineral na qualidade de mudas e da madeira de teca e paricá - Vieira, Cristiane Ramos (2015)
The incorrect fertilization management limits the seedlings growth in the nursery and on the field, prejudicing the obtaining of forest products. For this, two experiments was installed with the aim to analyze the growth of Tectona grandis and Schizolobium amazonicum [Schizolobium parahyba var. amazonicum] at different levels of NPK in order to characterize their quality in the nursery and in the field, and indicate the effects of fertilization on wood quality on the 1º year after the planting. Fot this, it was used Cambisol of loamy sand, limestoned considering base saturation of 50%. After, the fertilizer was realized in factorial 4x4x4: N = 0, 40, 80 and 120 kg ha-1 with urea PA; P2O5 = 0, 50, 100 and 200 kg ha-1 , with super simple; K2O = 0, 50, 100 and 200 kg ha-1 KCl PA. The seedlings were grown and when they reach 15 cm were transplanted to plastic bags containing soil limestoned and fertilized. For growth analysis, measurements were taken of height, diameter, biomass, macro and micronutrients at 180 days. The data were analyzed in a factorial design. After 180 days, the seedlings, submitted to treatments that provided the greatest growth, were transplanted to the field on planting hole previously limestoned and fertilized, staying for 12 months. Then, the plants were analyzed for the levels of ash and carbon. In the case of T. grandis, fertilization with 80 kg ha-1 N, 50 kg ha-1 of P2O5 and 100 kg ha-1 of K2O was the one that provided the highest growth in the nursery and in the field; the best combinations with NPK were 80 kg ha-1 N, 0 kg ha-1 of P2O5 and 50 kg ha-1 of K2O and 120 kg ha-1 N, 100 kg ha-1 P2O5 and 50 kg ha-1 K2O. These fertilizations for T. grandis showed greater growth in height, diameter and biomass and appropriate values for the ash content, total carbon and the C/N relation. About S. amazonicum, the fertilization more favored the seedlings growth was 120 kg ha-1 N, 100 kg ha-1 of P2O5 and 50 kg ha-1 of K2O in the nursery. And in the field, 0 kg ha-1 N, 200 kg ha-1 of P2O5 and 50 kg ha-1 of K2O, providing the greater growth in height, diameter and biomass and appropriate values for the ash content, total carbon and the C/N relation. The NPK fertilizer influenced the growth of T. grandis and S. amazonicum in the nursery and in the field, and the levels of ash content and carbon. In both cases, these results suggest the use of young wood these species for use as charcoal.